Pengamatan Efek Magnetooptis Menggunakan Interferometer - Fahrurazi, Michelson; Firdausi, Ketut Sofjan; Budi, Wahyu Setia (JURNAL SAINS DAN MATEMATIKA, 2006)
ABSTRACT---The magnetooptic effect of transparency material such as aquarium glass, acrylic, and micro slide has been studied using Michelson Interferometer. The change of refractive index to magnetic field B is obtained by placement of samples in a coil applied on altered field 0-0,2 T. Results of interferometer test show that change of refractive index is linearly dependent on B for acrylic and slide. However, for aquarium glass, it is on B2 dependency. This result is agreement to previous experiment that the structure of acrylic and slide is formed more regular as B applied. Keywords: Magnetooptic effect, refraction index, interferometer